2018
DOI: 10.21815/jde.018.030
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Dental Students About Incarceration and Correctional Dentistry: Results from a National Survey

Abstract: People who are incarcerated or have a history of incarceration have high rates of dental disease, but access to dental treatment is often a challenge during and after incarceration. Dental students' exposure to this population is unknown: no data exist regarding the number of schools that provide didactic and clinical training in correctional dentistry. The aim of this study was to assess the extent of instruction in correctional dentistry and clinical opportunities at correctional facilities for dental studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 36 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…However, our study provides an important caveat to the previously reported positive outcomes of other studies in correctional health settings (Applebaum et al 2002;Alemagno et al 2004;Weiskopf 2005;Dhawan et al 2007;Haley et al 2009;Rich et al 2012;Filek et al 2013;Diaz et al 2014;Bouchaud and Swan 2017;Simon et al 2017;van de Mortel et al 2017;Brooker et al 2018;Candamo et al 2018). Our data suggests a more cautionary approach may be required before immersing medical trainees (or their proctors) in correctional healthcare settings.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, our study provides an important caveat to the previously reported positive outcomes of other studies in correctional health settings (Applebaum et al 2002;Alemagno et al 2004;Weiskopf 2005;Dhawan et al 2007;Haley et al 2009;Rich et al 2012;Filek et al 2013;Diaz et al 2014;Bouchaud and Swan 2017;Simon et al 2017;van de Mortel et al 2017;Brooker et al 2018;Candamo et al 2018). Our data suggests a more cautionary approach may be required before immersing medical trainees (or their proctors) in correctional healthcare settings.…”
Section: Discussionmentioning
confidence: 51%
“…Reflective of other studies (Alemagno et al 2004;Kuthy et al 2007;Brooker et al 2018) and the rationale behind greater AMC involvement in correctional care (Raimer and Stobo 2004;Wakeman and Rich 2010;Pelletier 2015;Trestman et al 2015), our findings suggest that correctional care training-singular among other traditional care settingsprovides a unique opportunity to engage with the personhood of the patient by challenging prevailing stereotypes of the incarcerated and potentially other vulnerable communities. Here, we find some synergy with the aims of AMCs to create clinical experiences for medical learners that foster favorable attitudes to providing health care in prisons and reduce stigma towards those who are in custody or recently released (Faulkner and McCurdy 2000;Littlewood et al 2005;Wakeman and Rich 2010;Min et al 2012;Brooker et al 2018;Candamo et al 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Only one publication focused on the correctional experience of health professions trainees, although these experiences, if positive, can represent an opportunity to cultivate and recruit a future correctional workforce as well as train community providers aware of the health hazards associated with incarceration (Candamo et al, 2018; Simon & Tobey, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Such issues may be partly responsible for the difficulty many facilities face in recruiting and retaining providers (Kalra et al, 2016). Indeed, there is limited exposure to correctional settings for health trainees (Candamo et al, 2018; Simon & Tobey, 2019) and a lack of standardized competencies specific to correctional clinicians (Haley et al, 2009).…”
mentioning
confidence: 99%
“…To our knowledge, this report represents the first description of lessons learned from a student clinic in a correctional facility. Given that a substantial number of health professional schools offer some correctional exposure, programs may find value in the lessons learned and educational results detailed herein (Candamo, Tobey, & Simon, 2018).…”
Section: Discussionmentioning
confidence: 99%